Rapid response to eating disorder treatment: A systematic review and meta‐analysis. Issue 10 (16th August 2016) - Linardon, Jake; Brennan, Leah; de la Piedad Garcia, Xochitl
ABSTRACT: Objective: This review aimed to (a) examine the effects of rapid response on behavioral, cognitive, and weight‐gain outcomes across the eating disorders, (b) determine whether diagnosis, treatment modality, the type of rapid response (changes in disordered eating cognitions or behaviors), or the type of behavioral outcome moderated this effect, and (c) identify factors that predict a rapid response. Method: Thirty‐four articles met inclusion criteria from six databases. End of treatment and follow‐up outcomes were divided into three categories: Behavioral (binge eating/purging), cognitive (EDE global scores), and weight gain. Average weighted effect sizes(r) were calculated. Results: Rapid response strongly predicted better end of treatment and follow‐up cognitive and behavioral outcomes. Moderator analyses showed that the effect size for rapid response on behavioral outcomes was larger when studies included both binge eating and purging (as opposed to just binge eating) as a behavioral outcome. Diagnosis, treatment modality, and the type of rapid response experienced did not moderate the relationship between early response and outcome. The evidence for weight gain was mixed. None of the baseline variables analyzed (eating disorder psychopathology, demographics, BMI, and depression scores) predicted a rapid response. Discussion: As there is a solid evidence base supporting the prognostic importance of rapid response, the focus should shift toward identifying the within‐treatment mechanisms that predict a rapid response so that the effectiveness of eating disorder treatment can be improved. There is a need for future research to use theories of eating disorders as a guide to assess within‐treatment predictors of rapid response. © 2016 Wiley Periodicals, Inc. Int J Eat Disord 2016; 49:905–919